2007
DOI: 10.1093/treephys/27.10.1433
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compound emission from holm oak infested by gypsy moth larvae: evidence for distinct responses in damaged and undamaged leaves

Abstract: Foliage of Quercus ilex L. (holm oak), a widespread Mediterranean species, constitutively emits large quantities of a complex genotype-dependent mixture of volatile organic compounds (VOCs). During a mass outbreak of gypsy moth (Lymantria dispar L.) in southern France, we examined the effects of gypsy moth feeding on VOC production from whole apices and single leaves of Q. ilex. Feeding induced the emission of new VOCs at rates up to 240 ng m(-2) s(-1) (16% of the total VOC release), which mainly consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 53 publications
3
63
0
Order By: Relevance
“…In accordance with previous reports of holm oak terpene emissions, we found that the blend produced by holm oak saplings was composed mainly of α-and β-pinene, sabinene and myrcene (Street et al 1997;Staudt and Bertin 1998). Recently, Staudt and Lhoutellier (2007) showed that massive outbreaks of the gypsy moth (Limantria dispar) raise by 16% the total emitted VOCs, including new compounds, in Q. ilex after a delay of several hours from the start of the infestation. The presence of this moth promotes the release of DMNT, germacrene D, β-caryophyllene, and several other sesquiterpenes that were not emitted or emitted only in trace amounts from non-infested leaves.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with previous reports of holm oak terpene emissions, we found that the blend produced by holm oak saplings was composed mainly of α-and β-pinene, sabinene and myrcene (Street et al 1997;Staudt and Bertin 1998). Recently, Staudt and Lhoutellier (2007) showed that massive outbreaks of the gypsy moth (Limantria dispar) raise by 16% the total emitted VOCs, including new compounds, in Q. ilex after a delay of several hours from the start of the infestation. The presence of this moth promotes the release of DMNT, germacrene D, β-caryophyllene, and several other sesquiterpenes that were not emitted or emitted only in trace amounts from non-infested leaves.…”
Section: Discussionsupporting
confidence: 92%
“…In general, phloem feeders induce lower emissions of plant volatiles compared with chewing insects, even under high levels of plant infestation (Staudt and Lhoutellier 2007). Aphids are all phloem feeders, and their feeding behavior comprises two phases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an incidence may act as a contribution to non-stomatal O 3 sinks which should be kept in mind, especially for highly reactive sesquiterpenes, which may contribute by ozonolysis within the canopy (Jardine et al, 2011). However, sequiterpene emission from healthy holm oak is negligible (Staudt and Houtellier, 2007). Further-more, based on the results of our experiment under laboratory conditions, we conclude that due to the short residence time of 3.4 minutes, a contribution of gas phase reactions with O 3 and monoterpenes from the internal leaf tissue to the nonstomatal deposition is low.…”
Section: Flux Measurements Under Laboratory Conditionsmentioning
confidence: 99%
“…Although numerous studies have demonstrated that the VOC increase occurs in many plant species caused by many insect species (e.g. Blande et Brilli et al, 2009;Staudt and Lhoutellier, 2007), differences between the pine and spruce scale-up factors indicate that different tree species may have very different responses to bark beetle attacks. We include these two scenarios here in an effort to characterize this range of responses.…”
Section: A R Berg Et Al: the Impact Of Bark Beetle Infestations Onmentioning
confidence: 99%